Cyclophilin-B Modulates Collagen Cross-linking by Differentially Affecting Lysine Hydroxylation in the Helical and Telopeptidyl Domains of Tendon Type I Collagen - Terajima, Masahiko (J Biol Chem, 2016)
Covalent intermolecular cross-linking provides collagen fibrils with stability. The cross-linking chemistry is tissue-specific and determined primarily by the state of lysine hydroxylation at specific sites. A recent study on cyclophilin B (CypB) null mice, a model of recessive osteogenesis imperfecta, demonstrated that lysine hydroxylation at the helical cross-linking site of bone type I collagen was diminished in these animals (Cabral, W. A., Perdivara, I., Weis, M., Terajima, M., Blissett, A. R., Chang, W., Perosky, J. E., Makareeva, E. N., Mertz, E. L., Leikin, S., Tomer, K. B., Kozloff, K. M., Eyre, D. R., Yamauchi, M., and Marini, J. C. (2014) PLoS Genet. 10, e1004465). However, the extent of decrease appears to be tissue- and molecular site-specific, the mechanism of which is unknown. Here we report that although CypB deficiency resulted in lower lysine hydroxylation in the helical cross-linking sites, it was increased in the telopeptide cross-linking sites in tendon type I collagen. This resulted in a decrease in the lysine aldehyde-derived cross-links but generation of hydroxylysine aldehyde-derived cross-links. The latter were absent from the wild type and heterozygous mice. Glycosylation of hydroxylysine residues was moderately increased in the CypB null tendon. We found that CypB interacted with all lysyl hydroxylase isoforms (isoforms 1–3) and a putative lysyl hydroxylase-2 chaperone, 65-kDa FK506-binding protein. Tendon collagen in CypB null mice showed severe size and organizational abnormalities. The data indicate that CypB modulates collagen cross-linking by differentially affecting lysine hydroxylation in a site-specific manner, possibly via its interaction with lysyl hydroxylases and associated molecules. This study underscores the critical importance of collagen post-translational modifications in connective tissue formation.